2015
DOI: 10.1371/journal.ppat.1005311
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Protection via RdRP-Mediated Stable Activation of Innate Immunity

Abstract: For many emerging and re-emerging infectious diseases, definitive solutions via sterilizing adaptive immunity may require years or decades to develop, if they are even possible. The innate immune system offers alternative mechanisms that do not require antigen-specific recognition or a priori knowledge of the causative agent. However, it is unclear whether effective stable innate immune system activation can be achieved without triggering harmful autoimmunity or other chronic inflammatory sequelae. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 45 publications
3
50
0
1
Order By: Relevance
“…Pathogenic viruses may also share receptors or intracellular proteins/pathways also required by other viruses, thereby reducing their availability for viral replication. Innate antiviral responses may also be induced by potentially "protective" viruses that increase resistance to high-level replication by pathogenic viruses in the same (sapelovirus versus enterovirus) or different (parvovirus versus enterovirus) viral families (73)(74)(75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic viruses may also share receptors or intracellular proteins/pathways also required by other viruses, thereby reducing their availability for viral replication. Innate antiviral responses may also be induced by potentially "protective" viruses that increase resistance to high-level replication by pathogenic viruses in the same (sapelovirus versus enterovirus) or different (parvovirus versus enterovirus) viral families (73)(74)(75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Studies since the 1990s have indicated that expression of viral RdRp can activate the immune system and confer resistance to viral infection on plant cells (55)(56)(57). Several research groups have recently reported that expression of viral RdRps can also activate the innate immune system in mammalian cells (28,58,59). The RdRps of hepatitis C virus (HCV), Semliki Forest virus (SFV), and Theiler's murine encephalitis virus (TMEV) produce dsRNAs in transfected cells even in the absence of viral genomic RNA, and these dsRNAs, as pathogen-associated molecular patterns (PAMPs), are recognized by PRRs, which then trigger RLR/MAVS signaling pathway activation and induce IFN-I production.…”
Section: Discussionmentioning
confidence: 99%
“…As an allied but distinct point, the identification of dominant gain-of-function mutations in IFIH1 has highlighted the possibility of clinical nonpenetrance into old age in the presence of life-long, marked overexpression of ISGs (Rice et al, 2014). This situation is reminiscent of a mouse model where transgenic expression of a picornavirus RNA-dependent RNA polymerase (RdRP) leads to a dramatic up-regulation of ISG stimulation and profound viral resistance via an MDA5/MAVS-dependent pathway, but where the mice are entirely healthy (Painter et al, 2015). The contrast with mouse models also showing type I interferon up-regulation, but demonstrating a clear link between interferon expression and phenotype, might relate to the involvement of other inflammatory cytokines in the latter cases.…”
Section: Phenotypic Overlap and Differences Variable Expression And Nonpenetrancementioning
confidence: 99%